The repetitive DNA element BncDNA, enriched in the B chromosome of the cichlid fish Astatotilapia latifasciata, transcribes a potentially noncoding RNA - Ramos, Erica [UNESP] (2017)
Supernumerary chromosomes have been studied in many species of eukaryotes, including the cichlid fish, Astatotilapia latifasciata. However, there are many unanswered questions about the maintenance, inheritance, and functional aspects of supernumerary chromosomes. The cichlid family has been highlighted as a model for evolutionary studies, including those that focus on mechanisms of chromosome evolution. Individuals of A. latifasciata are known to carry up to two B heterochromatic isochromosomes that are enriched in repetitive DNA and contain few intact gene sequences. We isolated and characterized a transcriptionally active repeated DNA, called B chromosome noncoding DNA (BncDNA), highly represented across all B chromosomes of A. latifasciata. BncDNA transcripts are differentially processed among six different tissues, including the production of smaller transcripts, indicating transcriptional variation may be linked to B chromosome presence and sexual phenotype. The transcript lengths and lack of similarity with known protein/gene sequences indicate BncRNA might represent a novel long noncoding RNA family (lncRNA). The potential for interaction between BncRNA and known miRNAs were computationally predicted, resulting in the identification of possible binding of this sequence in upregulated miRNAs related to the presence of B chromosomes. In conclusion, Bnc is a transcriptionally active repetitive DNA enriched in B chromosomes with potential action over B chromosome maintenance in somatic cells and meiotic drive in gametic cells.